Determinants of Tourist Satisfaction and Dissatisfaction on Tourism Village - Putri Intan Sari; Yuliani Dwi Lestari (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2021)
Indonesia government established the development of tourism village as one of priority program. Until 2018, there are 1734 tourism villages in Indonesia. However, the increase of tourist visitation is not occurred evenly. Only several tourism villages are having high visitation rate, others are still struggling in competing with other tourism destinations. Previous study found that tourist satisfaction is leading on visit intention. Therefore, this study investigated factors determinant on tourist satisfaction and dissatisfaction of tourism village. A content analysis was adopted in this study by extracting of 464 tourist reviews that posted from January 2016 until October 2019. Data were collected from tourist review on TripAdvisor regarding nine tourism villages in Indonesia. NVivo 12 was used to analyse the data. The results revealed top 5 satisfaction determinant attributes: village landscape, friendliness local people, traditional building, traditional way of life, and village atmosphere. Meanwhile, dissatisfy tourist mention traditional souvenir, village atmosphere, village authenticity, village entrance fee, and the local people who become souvenir seller as the top 5 dissatisfaction attributes.